THE IMPACT OF THE COVID-19 PANDEMIC ON THE MENTAL HEALTH OF POPULATION OF SERBIA - Kovacevic, Nevenka (HEALTH CARE, 2023)
To date research in the field of mental health and COVID-19 disease revealed a variety of mental health responses and disorders during the COVID-19 pandemic. This paper represents an analysis of data published in professional and scientific papers and reports after research conducted on the impact of the COVID-19 pandemic on the mental health of both, general population, and vulnerable groups. According to the World Health Organization, during the first year of the pandemic, the global prevalence of anxiety and depression increased by as much as 25%. In the Republic of Serbia, according to the WHO data for 2017, 5% of the population lives with depression, and 3.8% with anxiety disorder. Many studies indicate that the state of emergency and quarantine during the COVID-19 pandemic had an impact on the mental health: 28.9% of adults had moderate to severe depression, and slightly more than ⅓ had anxiety and stress symptoms. During the state of emergency, out of 1103 young people aged 15-30, 19% felt vulnerable, and 16.3% very vulnerable. Young women, young people living in cities, and young people with higher level of education expressed greater vulnerability. During the state of emergency, 33.4% of respondents indicated that they felt their safety was threatened, 42.7% that their health was threatened, and most often they had fear related to the possibility of infecting family members, close friends and themselves. ¼ of respondents did not feel optimistic about the future, ⅓ felt completely useless, and 14.3% considered that their mental health had deteriorated greatly. Younger people felt that their mental health worsened less during health emergency, in comparison to older people. During the state of emergency, 11.1% of young people experienced violence, mostly verbal and online, and 10.4% physical violence. All the research conducted in the Republic of Serbia can be useful for planning interventions in the field of mental health, so that in the case of the emergence of new pandemics, the country will be ready to implement measures aimed at preserving mental health.
Keywords: mental health, pandemic, COVID-19